2008
DOI: 10.1074/jbc.m800294200
|View full text |Cite
|
Sign up to set email alerts
|

Cysteine Substitution Mutagenesis and the Effects of Methanethiosulfonate Reagents at P2X2 and P2X4 Receptors Support a Core Common Mode of ATP Action at P2X Receptors

Abstract: The agonist binding site of ATP-gated P2X receptors is distinct from other ATP-binding proteins. Mutagenesis on P2X 1 receptors of conserved residues in mammalian P2X receptors has established the paradigm that three lysine residues, as well as FT and NFR motifs, play an important role in mediating ATP action. In this study we have determined whether cysteine substitution mutations of equivalent residues in P2X 2 and P2X 4 receptors have similar effects and if these mutant receptors can be regulated by charged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
90
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(96 citation statements)
references
References 36 publications
5
90
1
Order By: Relevance
“…In addition, certain histidine residues within the protein can regulate P2X function [2,5]. It has been reported that glycine residues enhance flexibility in the extracellular loop, raising the possibility that they are involved in conformational changes in P2X receptors upon agonist binding [2,[76][77][78]. Swapping fragments and point mutations in the extracellular loop between rat and mouse P2X 7 receptors also demonstrated that amino acid residues in the ectodomain of the P2X 7 receptor are involved in the differential sensitivity to agonists between species [79].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, certain histidine residues within the protein can regulate P2X function [2,5]. It has been reported that glycine residues enhance flexibility in the extracellular loop, raising the possibility that they are involved in conformational changes in P2X receptors upon agonist binding [2,[76][77][78]. Swapping fragments and point mutations in the extracellular loop between rat and mouse P2X 7 receptors also demonstrated that amino acid residues in the ectodomain of the P2X 7 receptor are involved in the differential sensitivity to agonists between species [79].…”
Section: Discussionmentioning
confidence: 99%
“…Also indicated is the sequence alignment of the investigated segments (I to VI) of rat (r) and zebrafish (zf) P2X1-P2X4 and P2X7. Conserved residues previously identified as important for ATP function are underscored (12)(13)(14)(15)(16)(17)(18)(19). Pooled data in this and all other figures represent mean AE SEM.…”
Section: Resultsmentioning
confidence: 99%
“…On the basis of our P2X2 homology model (5), we individually mutated into cysteine 26 positions that protrude in the putative binding cavity, including those previously identified conserved residues (12)(13)(14)(15)(16)(17)(18)(19) (Fig. 1D).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In P2X [1][2][3][4][5][6][7] receptors from most other species, this site is occupied by a highly conserved KXK motif [17]. In human P2X 1 , rat P2X 2 , and rat P2X 4 , mutation of either of these two highly conserved lysines severely impaired ATP potency [20][21][22]. Fig.…”
Section: Cloning Of Zebrafish P2x Receptor Cdnas Uncovered Three New mentioning
confidence: 99%